2011
DOI: 10.1097/qad.0b013e328347f775
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior and HIV transmission risk of Ugandan adults taking antiretroviral therapy: 3 year follow-up

Abstract: Despite increased sexual activity among HIV-infected Ugandans over 3 years on ART, risky sex and estimated risk of HIV transmission remained lower than baseline levels. Integrated prevention programs could reduce HIV transmission in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 28 publications
6
59
2
Order By: Relevance
“…These differing approaches may be driven by evidence that treatment of the HIV-infected partner in a serodiscordant relationship significantly decreases the risk of HIV transmission. 28,29 Variability was also noted in frequency of follow up-visits: clinicians often preferred more frequent follow-up than is suggested by the guidance. Our findings are consistent with a prior study of HIV healthcare providers which found departure from the CDC guidance recommendations in testing for HIV infection, confirming high risk for acquiring HIV infection, screening/treatment for STIs, and screening for Hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…These differing approaches may be driven by evidence that treatment of the HIV-infected partner in a serodiscordant relationship significantly decreases the risk of HIV transmission. 28,29 Variability was also noted in frequency of follow up-visits: clinicians often preferred more frequent follow-up than is suggested by the guidance. Our findings are consistent with a prior study of HIV healthcare providers which found departure from the CDC guidance recommendations in testing for HIV infection, confirming high risk for acquiring HIV infection, screening/treatment for STIs, and screening for Hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…This provides some insight into how people manage their social relationships, particularly managing new sexual partnerships while on treatment. 18 However, the strategies people use in resource-limited settings to complete the tasks of living with ART, have not been covered in depth. 19 This article aims to describe self-management tasks experienced and strategies used by people living with ART in central Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…14 The studies conducted to date on heterosexual serodiscordant couples indicate that the small number of documented HIV transmissions occurred from individuals who had recently started therapy and in whom it is unlikely that undetectable viral load was achieved. 13,14,18 Our previous study, 12 together with two others, 8,19 have been identified 20 as the only ones in which full viral suppression was confirmed in the index cases under HAART. Pooled transmission rate for these studies was zero per 100 person-years (95% CI: 0-0.05).…”
Section: Discussionmentioning
confidence: 94%